A Novel Selective LSD1/KDM1A Inhibitor Epigenetically Blocks Herpes Simplex Virus Lytic Replication and Reactivation from Latency - Yu Liang (American Society for Microbiology, 2013)
ABSTRACT Cellular processes requiring access to the DNA genome are regulated by an overlay of epigenetic modifications, including histone modification and chromatin remodeling. Similar to the cellular host, many nuclear DNA viruses that depend upon the host cell’s transcriptional machinery are also subject to the regulatory impact of chromatin assembly and modification. Infection of cells with alphaherpesviruses (herpes simplex virus [HSV] and varicella-zoster virus [VZV]) results in the deposition of nucleosomes bearing repressive histone H3K9 methylation on the viral genome. This repressive state is modulated by the recruitment of a cellular coactivator complex containing the histone H3K9 demethylase LSD1 to the viral immediate-early (IE) gene promoters. Inhibition of the activity of this enzyme results in increased repressive chromatin assembly and suppression of viral gene expression during lytic infection as well as reactivation from latency in a mouse ganglion explant model. However, available small-molecule LSD1 inhibitors are not originally designed to inhibit LSD1, but rather monoamine oxidases (MAO) in general. Thus, their specificity for and potency to LSD1 is low. In this study, a novel specific LSD1 inhibitor was identified that potently repressed HSV IE gene expression, genome replication, and reactivation from latency. Importantly, the inhibitor also suppressed primary infection of HSV in vivo in a mouse model. Based on common control of a number of DNA viruses by epigenetic modulation, it was also demonstrated that this LSD1 inhibitor blocks initial gene expression of the human cytomegalovirus and adenovirus type 5. IMPORTANCE Epigenetic mechanisms, including histone modification and chromatin remodeling, play important regulatory roles in all cellular processes requiring access to the genome. These mechanisms are often altered in disease conditions, including various cancers, and thus represent novel targets for drugs. Similarly, many viral pathogens are regulated by an epigenetic overlay that determines the outcome of infection. Therefore, these epigenetic targets also represent novel antiviral targets. Here, a novel inhibitor was identified with high specificity and potency for the histone demethylase LSD1, a critical component of the herpes simplex virus (HSV) gene expression paradigm. This inhibitor was demonstrated to have potent antiviral potential in both cultured cells and animal models. Thus, in addition to clearly demonstrating the critical role of LSD1 in regulation of HSV infection, as well as other DNA viruses, the data extends the therapeutic potential of chromatin modulation inhibitors from the focused field of oncology to the arena of antiviral agents.